2020
DOI: 10.1093/femsec/fiaa016
|View full text |Cite
|
Sign up to set email alerts
|

Total RNA sequencing reveals multilevel microbial community changes and functional responses to wood ash application in agricultural and forest soil

Abstract: Recycling of wood ash from energy production may counteract soil acidification and return essential nutrients to soils. However, wood ash amendment affects soil physicochemical parameters that control composition and functional expression of the soil microbial community. Here, we applied total RNA sequencing to simultaneously assess the impact of wood ash amendment on the active soil microbial communities and the expression of functional genes from all microbial taxa. Wood ash significantly affected the taxono… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 87 publications
1
27
0
Order By: Relevance
“…The results showed that the effect of planting yellow horn on bacteria in y ash was much greater than that on fungi. Bang-Andreasen et al also found that the in uence of wood ash application on the abundance and diversity of bacteria in agricultural and forest soil was greater than that of fungi [35].…”
Section: Discussionmentioning
confidence: 96%
“…The results showed that the effect of planting yellow horn on bacteria in y ash was much greater than that on fungi. Bang-Andreasen et al also found that the in uence of wood ash application on the abundance and diversity of bacteria in agricultural and forest soil was greater than that of fungi [35].…”
Section: Discussionmentioning
confidence: 96%
“…Extracellular DNA is relatively stable and only slowly degrades in soils 62,63 and the inclusion of DNA from dead organisms will thus indicate slower community responses than what is actually true in the soil 64 . Total RNA-sequencing would circumvent the bias associated with relic DNA as RNA have much faster turnover time [65][66][67] . We therefore suggest that future studies should also consider RNA-based techniques when studying short-time reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Wood ash amendment can affect soil physicochemical parameters and influence soil microbial community composition and functional expression, primarily related to soil chemical properties (increased pH, electrical conductivity, dissolved organic carbon, and phosphate) (Bang-Andreasen et al, 2020). Addition of the wood ash amendments caused an increase in genes associated with copiotrophic microbial subpopulations (rRNA); in general, more functional genes (mRNA) were observed to be upregulated than downregulated, with the majority originating from four functional categories: "post-translation modification, protein turnover and chaperones"; "transcription"; "replication, recombination, and repair"; and "carbohydrate transport and metabolism"-genes that are involved with carbon cycling (i.e., metabolism and cell growth) (Bang-Andreasen et al, 2020). The researchers concluded that increases in pH, bioavailable dissolved organic carbon, and nutrients (induced by the wood ash ammendments) allow copiotrophic groups to thrive at the expense of oligotrophic groups directly following amendment application.…”
Section: Metatranscriptomics-general Context and Current Applicationsmentioning
confidence: 99%